(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the main aspects of labor training for students of schools of I and II types; the relationship between labor activity and the solution of a number of correctional and developmental tasks; the necessary requirements for high school students in labor training are analyzed.